Analysis of acceptability of HIV, TB, and material health services: a case study of a Johannesburg sub-district, South Africa - Blaise, Bucyibaruta Joy (My University, 2016)
Background: Access to HIV/AIDS, tuberculosis (TB) and maternal health (MH) services in developing countries, including South Africa, remains inadequate and inequitable as cited by some authors including Harris et al. (2011) as well as Silal et al. (2012). The concept of access to health services has evolved significantly over the past years to recognise three dimensions: availability, affordability and acceptability, as put forward by McIntyre et al. (2009). Nevertheless, most published studies on access to HIV, TB and maternal health services have focussed on availability and affordability, leaving acceptability neglected and poorly conceptualized. Objectives: This study aimed at developing an acceptability index to identify and explore factors influencing acceptability of health services using the experiences of patients attending public HIV, TB and Maternal Health care in a sub-district of Johannesburg between 2008 and 2010. Design: Mixed methods were used to analyse secondary data collected as part of the Researching Equity in Access to Health Care (REACH) study. The analysis was guided by a conceptual framework of acceptability comprising three elements - provider, service and community – as suggested by Lucy Gilson (2007). STATA was used for descriptive and inferential analysis of quantitative data. Unit weighted composite scores were used to develop acceptability indices. The p value <0.05 was considered statistically significant. The in-depth interview transcripts were analysed thematically using ‘acceptability themes’ obtained deductively and inductively. The quantitative and qualitative findings were triangulated during discussion of the results. Results: This study analysed 987 patients’ exit interviews, clinical records, self-reporting and 15 in-depth interviews. The results showed that only 23.4% of patients seeking HIV services experienced high overall acceptability. In contrast, overall acceptability was high for most users of the TB (97.3%) and MH (90.1%) tracers. Provider acceptability was consistently high across all the tracers at 97.6% (HIV) 96.6% (TB) and 96.4% (MH). Service acceptability was high only for TB (70.1%). Community acceptability was high for both TB (83.6%) and MH (96.8%) tracers. Patients aged over 40 years were 1.7 times more likely to have HIV-service high acceptability than those aged 40 years and below (p=0.026). The community acceptability decreased by 0.6 unit (p= 0. 003), while the MH-overall acceptability decrease by 0.1 units (p=0.045) when age increased by 1 unit. Male patients were 1.9 times more likely to have HIV-service high acceptability (p=0.023), but 2.5 times less likely to have high community acceptability than female patients (p = 0.029). The individuals from a middle socio-economic class were 26.4 times more likely to have HIV-provider high acceptability (p=0.024), and 7.4 times more likely to have MH-provider high acceptability (p= 0.034) than their poorer counterparts. Staying with three or more adults in the household was associated with high community acceptability for both HIV and MH tracers. Limitations: Lack of control over the questionnaire design, data collection process (secondary data analysis), missing values such as some patients did not have records like CD4 count, VL, ART-support group (for ART service), smear culture results, missing clinical visits, missing taking TB tablets (for TB service), HIV status, Type of delivery, booking status (for MH service) and out-dated data in view of rapid changing policies around HIV, TB and MH services were important barriers. Conclusion: Analysis of different elements of acceptability is necessary to gain better understanding of, and feed evidence into policy for, improving health service acceptability. Various demographic, socio-economic and clinical factors may affect different elements of acceptability. This study noted high overall acceptability of TB and MH services as opposed to low acceptability of ART. This low acceptability of ART could be explained partly by HIV stigma at the time of REACH data collection -though since then the stigma has significantly decreased Further studies integrating all elements of acceptability and recognising the multiple aspects of each element are needed to provide strong evidence to guide health policies and interventions to improve the acceptability of health services.
DISSERTATION SUBMITTED IN PARTIAL FULFILLMENT OF REQUIREMENTS FOR A MASTER OF PUBLIC HEALTH (MPH) IN HEALTH SYSTEM AND POLICY (HSP). 31 August 2016